Improving EFL Students’ Reading Comprehension and Critical Thinking Skill through Directed Reading Thinking Activity - Karolis Anaktototy; Inggrid Lesnussa (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2022)
Abstract. Reading comprehension and critical thinking skills are pivotal skills which can trigger academic achievements of students in the English Foreign Language Learning. This study was conducted to improve those students’ reading comprehension and critical thinking skills by implementing Directed Reading Thinking Activity (DRTA). The researcher conducted the study by following the classroom action research approach that consists of four steps in each of its cycles consisting of planning, action, observation, and reflection. The researcher used pre-test, post-test, and questionnaire to collect the data. The data from the result of tests were analyzed quantitatively while the observation results were analyzed qualitatively. The study results show that the implementation of DRTA can improve students' reading comprehension and critical thinking skills. DRTA can improve students reading skills and critical thinking because the DRTA strategy focuses on student engagement with the text. Hence, students have to predict and prove when the students read, and it makes the learning process more interactive and the students more active. Thus, the researcher recommends DRTA for those teachers who find similar problems in improving students’ reading comprehension and critical thinking. Keywords: Critical Thinking, Directed Reading Thinking Activity, Reading Comprehension